Magnetism in diamond graphene nanoflakes - Thu, Phung Thi; Mai, Nguyen Thi; Lien, Pham Thi; Tung, Nguyen Thanh (Vietnam Journal of Science and Technology, 2023)
We numerically study in this work the magnetic properties induced by the on-site electron-electron interaction in graphene nanoflakes shaped diamond with a variety of sizes. By the mean-field Hubbard approximation, a phase transition in analogy to infinite graphene from non-magnetism to antiferromagnetism is observed. A very weak interaction U, approximately zero, is reported to be able to trigger magnetic ordering in a finite nanoflake compared to infinite structure. Furthermore, the investigation also indicates the edge and size dependence of magnetism. The antiferromagnetic ground state is of robust stability to larger zigzag nanoflake size and stronger interaction. The phase transition point, Uc, is found to be sensitive to the size denoted by means of the reduction of Uc as the size increases. The important role of edge effect causing the spin polarization along zigzag termination is confirmed for the diamond nanoflakes.